MEDICAL INDICATIONS OF SECTIO CAESAREA IN GENERAL DISTRICT HOSPITAL OF PARE KEDIRI YEAR 2013 – 2015 - Brivian Florentis Yustanta (STIKES Karya Husada Kediri, 2015)
Sectio caesarea is a surgical operation to deliver baby by opening uterus, as the last alternative problem solving in labour which must consider medical indications. Within last 20 years, occurence of sectio caesarea is increasing from 5% become 20%. According to Indonesian Health Ministry (2010), the number of sectio caesarea in goverment hospital is about 20-25% from total labor. Researcher wants to know the sectio caesarea phenomenon which is increasing year by year with present the data about the sectio caesarea indications in General District Hospital of Pare Kediri year 2013 – 2015. This is descriptive research. The population was all of mothers whom have delivered in sectio caesarea in General District Hospital of Pare Kediri, at 2013 was amount 167 mothers, at 2014 was amount 369 mothers, and at 2015 was amount 461 mothers. This was using total sampling technique. Data collection by secondary data from medical record. The result research showed that sectio caesarea from 2013 until 2015 kept on increasing. At 2013 the number of sectio caesarea 25,9% from total labor, at 2014 increased into 33% from total labor, and at 2015 was 35,8% from total labor. The greatest indication at 2013 was failure of labor induction (26,9%), at 2014 was sectio caesarea history (22,8%), and at 2015 was sectio caesarea history (21,7%). During implementing sectio caesarea have to pay attention to conditions, requisites and indications before, so it won’t cause any new suffering as well as reach raising of mother and child health level